2021
DOI: 10.1002/joc.7203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cloud microphysical parameterization on the characteristics of monsoon depressions over the Indian region

Abstract: Indian summer monsoon (ISM) low‐pressure systems are considered as the lifeline for seasonal monsoon rainfall over the Indian region. However, the current models have limitations in predicting their characteristics and rainfall. This study assesses the influence of five cloud microphysical parameterization Schemes (MP) on simulations of 14 monsoon deep depressions (DD) using the weather research and forecasting (WRF) model. The simulations are carried out with a lead time up to 96 hr in a nested domain resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It usually has a warm core overlying the low-level cold core surrounded by strong wind aloft due to the strong latent heating in the troposphere from convective precipitation. Most of previous studies focused on the track and structure of the monsoon depression and its influence on the precipitation of South Asia (Baisya et al, 2017;Hazra & Pattnaik, 2021;Hunt & Fletcher, 2019;Hunt & Turner, 2017;Hunt et al, 2016;Johnson et al, 2016;Pattanaik et al, 2011;Potty et al, 2000), wherein the monsoon depression has been proved to be sensitive to model horizontal resolution, microphysical scheme, and convective parameterization etc. For example, Johnson et al (2016) investigated the simulated South Asian Monsoon at resolutions from 1.9°to 0.35°(approximately 200-40 km) and found that monsoon depressions strengthened precipitation over the northeastern India with increased resolution.…”
Section: Introductionmentioning
confidence: 99%
“…It usually has a warm core overlying the low-level cold core surrounded by strong wind aloft due to the strong latent heating in the troposphere from convective precipitation. Most of previous studies focused on the track and structure of the monsoon depression and its influence on the precipitation of South Asia (Baisya et al, 2017;Hazra & Pattnaik, 2021;Hunt & Fletcher, 2019;Hunt & Turner, 2017;Hunt et al, 2016;Johnson et al, 2016;Pattanaik et al, 2011;Potty et al, 2000), wherein the monsoon depression has been proved to be sensitive to model horizontal resolution, microphysical scheme, and convective parameterization etc. For example, Johnson et al (2016) investigated the simulated South Asian Monsoon at resolutions from 1.9°to 0.35°(approximately 200-40 km) and found that monsoon depressions strengthened precipitation over the northeastern India with increased resolution.…”
Section: Introductionmentioning
confidence: 99%
“…It usually has a warm core overlying the low-level cold core surrounded by strong wind aloft due to the strong latent heating in the troposphere from convective precipitation. Most of previous studies focuses on the track and structure of the monsoon depression and its influence on the precipitation of South Asia (Baisya et al, 2017;Hazra & Pattnaik, 2021;Hunt et al, 2016;Hunt & Fletcher, 2019;Hunt & Turner, 2017;Pattanaik et al, 2011;Potty et al, 2000), wherein the monsoon depression has been proved to be sensitive to model horizontal resolution, microphysical scheme, and convective parameterization etc. So far, only minimal studies investigated the impacts of resolution across hydrostatic to non-hydrostatic scales on regional-scale systems, such as the monsoon depression system, and then on the moisture transport over the TP.…”
Section: Introductionmentioning
confidence: 99%
“…Using satellite data (tropical rainfall measuring mission [TRMM] precipitation radar), Stano et al (2002) performed a composite study and showed that stratiform rain was found to be aroused where the melting layers were located near 5 km from the surface; they were able to capture some more features of MD, for example, melting layer, melting layer, and so forth. Hazra and Pattnaik (2021) conducted a composite study using 14 deep depressions over the eastern India region. They found that the WRF double-moment scheme has a more significant edge in predicting the rainfall (compared with TRMM data) over other MP schemes.…”
Section: Introductionmentioning
confidence: 99%